2019
DOI: 10.3390/aerospace6120129
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polyisobutylene Kerosene Additive on Combustion Efficiency in a Liquid Propellant Rocket Engine

Abstract: The combustion of kerosene with the polymer additive polyisobutylene (PIB) was experimentally investigated. The aim of the study was to measure the effect of PIB kerosene on the efficiency of combustion chamber cooling and the combustion efficiency of the liquid propellant for a rocket engine operating on kerosene and gaseous oxygen (GOX). The study was conducted on an experimental rocket engine using kerosene wall film cooling in the combustion chamber. Fire tests showed that the addition of polyisobutylene t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…According to this idea, the molecular structure of each component is shown in Figure 1. Experimental studies have shown that polyisobutene used in combustion chamber cooling channels can significantly reduce pressure loss [26], so polyisobutene was selected as the drag reduction agent (DRA). The polymer chains were composed of NS monomers.…”
Section: System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this idea, the molecular structure of each component is shown in Figure 1. Experimental studies have shown that polyisobutene used in combustion chamber cooling channels can significantly reduce pressure loss [26], so polyisobutene was selected as the drag reduction agent (DRA). The polymer chains were composed of NS monomers.…”
Section: System Modelmentioning
confidence: 99%
“…Acco idea, the molecular structure of each component is shown in Figure 1. E studies have shown that polyisobutene used in combustion chamber cooling c significantly reduce pressure loss [26], so polyisobutene was selected a reduction agent (DRA). The polymer chains were composed of NS monom initial stage, Np polymer chains were randomly distributed in the simulatio polymer chains with different lengths were considered: NS = 36 and NS = 60.…”
Section: System Modelmentioning
confidence: 99%